A Wired Laccase Oxygen Cathode with Carboxylated Single‐Walled Carbon Nanotubes Incorporated. (9th July 2020) - Kim, Sujeong; Shin, Hyosul; Kang, Chan
Abstract : The wired laccase cathode with the incorporation of single‐walled carbon nanotubes (SWNTs) functionalized with carboxyl groups was constructed. As the wiring redox polymer, the copolymer of polyacrylamide and poly( N ‐vinylimidazole) complexed with [Os(2, 2′;6′2″‐terpyridine)(4, 4′‐dimethyl‐2, 2′‐bipyridine)] 2+/3+ (PAA‐PVI‐[Os(tpy)(dme‐bpy)2 ] 2+/3+ ) was used. The prepared laccase cathode was applied for the electrocatalytic reduction of oxygen. With the addition of the carboxylated carbon nanotubes (CNT‐COOHs), in comparison to the result with no CNT‐COOHs included, the catalytic O2 reduction current density increased from 0.35 mA/cm 2 to 0.59 mA/cm 2 at the cathode under the condition of a 500 rpm electrode rotation speed in an air‐saturated pH 5.0 2.0 M citrate buffer at 37°C. Other effects showing less current decreases with halide ion additions and enhanced stability, when CNT‐COOHs were included, were also observed. Abstract : Construction of a wired laccase oxygen cathode with carboxylated single‐walled carbon nanotubes incorporated